Manifestation of Heat-Induced Valuable Dietary Nucleotide Salvage in Food Prepared from Aged Fish in Fast Protein and Metabolites Liquid Chromatography, ATP-Bioluminescence Assay, and NMR Spectra - Alar Sünter; Artur Kuznetsov; Piret Raudsepp; Tõnu Püssa; Lauri Toom; Georgii Konoplev; Oksana S. Stepanova; Oksana V. Stepanova; Daniil Lyalin; Aleksandr Frorip; Mati Roasto (AppliedChem, 2023)
Dietary nucleotides and nucleosides, primarily inosine monophosphate (IMP) and the adenine nucleotide pool (ANP), are widely considered as essential nutrients responsible for multiple biological functions. Food prepared from meat and fish is the main source of these substances in the human diet, and it is extremely important to implement storage and processing techniques ensuring their maximum preservation and even accumulation during maturation or conditioning. In experiments with freshly refrigerated grass carp and defrosted Alaska pollock fillets it was discovered, initially using Fast Protein and Metabolites Liquid Chromatography and the ATP-bioluminescence test, and afterwards validated by NMR spectroscopy, that heat treatment identical to conventional culinary processing in aqueous or wet media at temperatures above 62 °C leads to nucleotide salvage (recovery) in aged fish. A significant increase in the concentration of IMP, and even an emergence of ANP substances, were reliably demonstrated in fish samples which had already partially or fully lost these components during prolonged storage due to the ATP breakdown metabolic reactions. Owing to this recovery, the nutritive value of ready-to-eat food can be higher than was initially evaluated in raw products before heat treatment: an effect that should certainly be considered in practical nutrition. Moreover, it is necessary to reconsider the widely acknowledged system of indices of freshness based on nucleotides and nucleosides elaborated a long time ago for raw meat and fish products.